Exploration of strategy: Objectives, competencies and competitive advantage - Ginevičius, Romualdas; Korsakiene, Renata (Journal of Business Economics and Management, 2005)
The notion that all companies should have a strategy is widely accepted. It has to be noted that a company's competitiveness describe objectives, competencies, competitive advantage and strategies. The linkages among objectives, competencies and competitive advantage are influenced by competitive forces in the market. The purpose of this paper is to propose a conceptual framework for analysis of a strategy and to present results of a survey carried out to explore the strategies of Lithuanian construction companies. The determinants of strategy such as objectives, competencies and competitive advantage can further be used as a guide for setting a strategic agenda for construction companies with different characteristics and operating in different markets.First Published Online: 14 Oct 2010